2003
DOI: 10.1016/s0002-9440(10)63604-8
|View full text |Cite
|
Sign up to set email alerts
|

Id4 Regulates Mammary Epithelial Cell Growth and Differentiation and Is Overexpressed in Rat Mammary Gland Carcinomas

Abstract: Id4 belongs to a family of helix-loop-helix (HLH) proteins that impact cellular growth and differentiation via regulation of basic HLH transcription factors. Herein the rat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 38 publications
2
47
2
Order By: Relevance
“…Others have found nuclear expression of Id-4 to be increased in the initiation and progression of breast cancer in rat. 24 Id-4 has been shown to positively correlate with invasion ability of a mouse breast cancer cell line in that same study. A significant association between Id-4 promoter hypermethylation and nodal metastasis in human breast cancer samples has been found.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Others have found nuclear expression of Id-4 to be increased in the initiation and progression of breast cancer in rat. 24 Id-4 has been shown to positively correlate with invasion ability of a mouse breast cancer cell line in that same study. A significant association between Id-4 promoter hypermethylation and nodal metastasis in human breast cancer samples has been found.…”
Section: Discussionmentioning
confidence: 73%
“…22 Id-4 expressions were shown to correlate with invasiveness of breast cancer cells 23 and breast carcinomas in mice. 24 However, another study has suggested that hypermethylation of Id-4, which leads to reduced gene expression, is significantly associated with node-positive T1 primary breast cancer. 25 These findings show that Id proteins may also be involved in metastasis of different types of cancer.…”
mentioning
confidence: 99%
“…ID family members including ID1, ID2, and ID3 have identified functions in tumor progression, including angiogenesis, invasion, and metastasis (Lyden et al, 1999;Benezra, 2001;Benezra et al, 2001;Folkman, 2002;Ruzinova and Benezra, 2003;, and in other circumstances ID1 and ID2 may function as tumor suppressors in rodents (Itahana et al, 2003;Sikder et al, 2003;Russell et al, 2004). The function of ID4 in tumorigenesis is similarly complex (Beger et al, 2001;Bellido et al, 2003;Chan et al, 2003;Shan et al, 2003;Umetani et al, 2004Umetani et al, , 2005 Jeon et al, 2008). ID4 seems to function as a tumor suppressor in a variety of cancers (Chan et al, 2003;Umetani et al, 2004Umetani et al, , 2005Yu et al, 2005) and is downregulated by promoter hypermethylation in several tumor types (Chan et al, 2003;Umetani et al, 2004Umetani et al, , 2005Yu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] The study of ID4 expression in breast cancers has also lead to conflicting results. The expression of rat Id4 was examined in rat induced mammary gland tumors by Shan et al 31 By real-time polymerase chain reaction analysis, relative expression of ID4 mRNA in carcinomas, adenomas and normal tissue was 27, 6 and 1, respectively. Immunohistochemical analysis indicated statistically significant elevated nuclear expression for Id4 protein in carcinomas compared to adenomas and normal mammary gland.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that these results implicate Id4 in rat mammary gland carcinogenesis and suggest that Id4 may contribute to carcinogenesis by inhibiting mammary epithelial cell differentiation and stimulating mammary epithelial cell growth. 31 More recently, Umetani et al assessed the methylation status of ID4 promoter CpG island by methylation-specific PCR (MSP) and ID4 mRNA level by quantitative real-time RT-PCR. Of the eight cell lines studied, ID4 mRNA level was suppressed in two fully methylated cell lines.…”
Section: Introductionmentioning
confidence: 99%